2023
DOI: 10.1021/acsomega.3c07034
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin-Ursodeoxycholic Bile Acid Hybrids in the Fight against SARS-CoV-2

Elena Marchesi,
Valentina Gentili,
Daria Bortolotti
et al.

Abstract: Here, we propose the molecular hybridization of dihydroartemisinin (DHA) and ursodeoxycholic bile acid (UDCA), approved drugs, for the preparation of antiviral agents against SARS-CoV-2. DHA and UDCA were selected on the basis of their recently demonstrated in vitro activity against SARS-CoV-2. A selection of DHA-UDCA-based hybrids obtained by varying the nature of the linkage and the bile acid conjugation point as well as unconjugated DHA and UDCA were tested in vitro for cytotoxicity and anti-SARS-CoV-2 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, they also have the common ability to cross the blood–brain barrier [ 8 , 19 ]. Quite curiously, during our recent research focused on KB activities as well as on the synthesis of KB derivatives, we found very little information about the combined activities of UDCA and KBs [ 20 ] and, in spite of the large number of BA conjugates reported in the literature [ 21 , 22 , 23 , 24 , 25 , 26 ], no article has reported the synthesis of covalent UDCA-KB conjugates (this is the same for the other BAs). In order to close this gap, in this work, we describe the enzymatic synthesis of new acetoacetic esters of UDCA.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, they also have the common ability to cross the blood–brain barrier [ 8 , 19 ]. Quite curiously, during our recent research focused on KB activities as well as on the synthesis of KB derivatives, we found very little information about the combined activities of UDCA and KBs [ 20 ] and, in spite of the large number of BA conjugates reported in the literature [ 21 , 22 , 23 , 24 , 25 , 26 ], no article has reported the synthesis of covalent UDCA-KB conjugates (this is the same for the other BAs). In order to close this gap, in this work, we describe the enzymatic synthesis of new acetoacetic esters of UDCA.…”
Section: Introductionmentioning
confidence: 99%